How Gender Differences in Entitlement and Apprehension Manifest Themselves in Negotiation - Najib A. Mozahem (14150970) (2022)
The gender difference in the propensity to initiate negotiation has been theorized to be mediated by three constructs: recognition of opportunities, entitlement, and apprehension. This study seeks to investigate whether differences in feminine and masculine traits can be used to explain gender differences in the three predictors of the propensity to initiate negotiations. Data was collected from 350 surveys distributed in Lebanon. Items were used to measure the constructs masculinity and femininity, as well as the three predictors of the propensity to initiate negotiation, namely Recognition of opportunities, Entitlement, and Apprehension. Confirmatory Factor Analysis was used to assess the validity of the measures, while structural equation modeling was used to investigate the relationship between the personality traits and the three constructs. Results indicate that masculinity enhances entitlement, which in turn leads to higher levels of negotiation while femininity enhances apprehension, which in turn leads to lower levels of negotiation. Both masculine and feminine traits were found to be positively related to the recognition of opportunities. Other Information Published in: Group Decision and Negotiation License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s10726-021-09724-3